A Review on the Role of Artificial Intelligence in Livestock Health Management - , Lalit Kumar; , Kaajal Nainwal; Sanjay,; , Pooja Nitharwal; , Yogendra Kumar Shukla; , Rashmi Shukla; , Pulkit Chugh (Archives of Current Research International, 2025)
Artificial Intelligence (AI) is transforming livestock health management by introducing practices that are guided by data, efficient, and environmentally sustainable. This paper examines how AI technologies are being applied in animal agriculture, emphasizing their contributions to live monitoring, illness detection, behavior tracking, and improving breeding processes. Utilizing machine learning, computer vision, and Internet of Things (IoT) tools, AI supports early health issue identification, enhances animal well-being, and boosts overall productivity. The discussion includes applications like automated health evaluations and advancements in reproductive success, alongside the significant impact of AI in managing poultry. Additionally, the study considers the hurdles of implementing AI, such as substantial costs, information security, and moral implications. In spite of these challenges, AI presents valuable opportunities for the advancement of precision livestock farming by promoting informed decisions and optimized use of resources. The paper finishes by projecting how AI could influence the future of livestock oversight through ongoing research, technological innovation, and supportive policies, all while maintaining ethical and sustainable practices in farming.